Chronic inflammatory demyelinating polyradiculoneuropathy relapse after mexiletine withdrawal in a patient with concomitant myotonia congenita: A case report on a potential treatment option. Issue 28 (10th July 2020) - Portaro, Simona; Biasini, Fiammetta; Bramanti, Placido; Naro, Antonino; Calabrò, Rocco Salvatore
Abstract: Introduction: we report on the first case of a woman affected by chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) and recessive myotonia congenita (MC), treated with mexiletine. We aimed at describing the possible role of mexiletine in CIDP management. Patient Concerns: A 44-year-old female affected by CIDP and MC, gained beneficial effects for CIDP symptoms (muscle weakness, cramps, and fatigue) and relapses, after mexiletine intake (200 mg twice a day). The patient presented with detrimental effects after mexiletine drop out, with a worsening of CIDP symptoms. Interventions: The patient reported a nearly complete remission of muscle stiffness and weakness up to 3 years since mexiletine intake. Then, she developed an allergic reaction with glottis edema, maybe related to mexiletine intake, as per emergency room doctors' evaluation, who suggested withdrawing the drug. Outcomes: The patient significantly worsened after the medication drop out concerning both CIDP and MC symptoms. Conclusion: This is the first report on the association of CIDP and MC in the same patient. Such diseases may share some clinical symptoms related to a persistent sodium currents increase, which maybe due either to the over-expression of sodium channels following axonal damage due to demyelination or to the chloride channel genes mutations. This is the possible reason why mexiletine maybe promising to treat CIDP symptoms.